Pemanfaatan Teknologi Informasi Bagi Masyarakat Desa Petak Dalam Proses Administrasi Desa - Luh Made Yulyantari; I Nyoman Rudy Hendrawan; Dwi Haryadi Nugraha; I Made Bhaskara Gautama; Ni Ketut Dewi Ari Jayanti; Gde Sastrawangsa; Ni Made Dewi Kansa Putri (Indonesian Journal Publisher, 2023)
Petak Village has utilized technology in the form of a village information system. However, this has not provided maximum convenience, especially for the Petak Village community. This is caused by the lack of maximum utilization of the information system in terms of community needs related to village administration. The lack of public knowledge about how to utilize the information system and the lack of outreach, make these features not be used as they should. The public service most often needed by the community is regarding village administration in the form of a statement letter from the village administration. So far, people have had to come directly to the village office and then apply for the certificate. The process of submitting this letter can be made more concise if using technological assistance. The solutions offered to these problems are divided into two types of activities, namely training on the use of technology, especially web-based, in facilitating activities in the village and holding training on the use of technology that has been provided by Petak Village Apparatuses in terms of village administration services for the community. The initial activity that has been carried out is training regarding the use of technology in the form of healthy internet training, namely digital literacy for the people of Petak Village. Evaluation of activities was carried out at the end of the training and showed an increase in the knowledge of the trainees by 4.875. The second service activity is training in the use of village information systems in submitting letters. The results of the evaluation of community service activities are 51% of community service activities which are stated to be very good.